Secularizing the sacred : aspects of Israeli visual culture - Mishory, Alec (Leiden ; Boston : Brill, 2019)
"As historical analyses of Diaspora Jewish visual culture blossom in quantity and sophistication, this book analyzes 19th-20th-century developments in Jewish Palestine and later the State of Israel. In the course of these approximately one hundred years, Zionist Israelis developed a visual corpus and artistic lexicon of Jewish-Israeli icons as an anchor for the emerging "civil religion." Bridging internal tensions and even paradoxes, artists dynamically adopted, responded to, and adapted significant Diaspora influences for Jewish-Israeli purposes, as well as Jewish religious themes for secular goals, all in the name of creating a new state with its own paradoxes, simultaneously styled on the Enlightenment nation-state and Jewish peoplehood"--
8.8 The Menorah's Penultimate Station on Its Way Home: Kssalon Settlement8.8.1 The Menorah's Last Station?; 8.9 Visual References to the Israeli Menorah Motif; Chapter 9 Zionism Liberates the Captured Daughter of Zion; 9.1 The Judaea capta Coin; 9.2 Jewish References to the Roman Judaea capta Coin; 9.3 From Judaea capta to Judaea liberata; 9.4 The Judaea capta Image on O˜˚˛cial Israeli Publications; 9.5 A Late Israeli Daughter of Zion; Chapter 10 The Twelve Tribes of Israel: from Biblical Symbolism to Emblems of a Mythical Promised Land
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
eBooks on EBSCOhost
Keywords: Art, Israeli -- History -- 20th century; Art, Modern -- 19th century -- History; Jewish art and symbolism -- Israel; Jewish art and symbolism -- Palestine; Zionism in art; Art israélien -- Histoire -- 20e siècle.; Art -- 19e siècle -- Histoire; Symbolisme juif -- Israël.; Symbolisme juif -- Palestine; Sionisme dans l'art.; Art, Modern; Art, Israeli; Jewish art and symbolism; Zionism in art; Israel; Middle East -- Palestine; 1800-1999; History